PENGARUH KEPUASAN KONSUMEN TERHADAP LOYALITAS PADA SEPEDA MOTOR SUZUKI DI PT. RIAU JAYA CEMERLANG UJUNGBATU KABUPATEN ROKAN HULU - -, Dasmiati (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
AbstractÂ The purpose of this study were (1) To determine customer satisfaction Suzuki motorcycle at PT. Riau Jaya Cemerlang Ujungbatu Rokanhulu districts (2) To determine customer loyalty on a motorcycle Suzuki PT. Riau Jaya Cemerlang Ujungbatu Rokanhulu district (3) To determine the effect of customer satisfaction on loyalty to the Suzuki motorcycle at PT. Riau Jaya Cemerlang. Variables used in this research is customer satisfaction (X) and customer loyalty (Y). The method used to analyze the research data is descriptive analysis and simple regression analysis. The data were processed using SPSS windows version 18 generate the regression equation Y = 5.486 + 0,342X. From this research, the adjusted R2 value of 0.496, this means 49.60% customer satisfaction effect on loyalty to the Suzuki motorcycle at PT. Riau Jaya district Ujungbatu Rokanhulu brilliantly and the rest is contributed by other variables not examined. The conclusion from this study is there Effect of consumer satisfaction to loyalty to the Suzuki motorcycle at PT. Riau Jaya Cemerlang Ujungbatu Rokanhulu district.